The jejunal cellular infiltrate in coeliac disease complicated by lymphoma. Issue 6 (June 1974) - Ferguson, R.; Asquith, P.; Cooke, W. T.
Abstract : Lymphocytes and plasma cells in the lamina propria and lymphocyte in the epithelium have been quantitated in jejunal biopsies from 18 patients with coeliac disease who developed lymphoma. In six patients two or more serial biopsies were available for study. Counts were compared with those obtained in 15 healthy controls and 30 other coeliacs, 15 of whom have been on a gluten-free diet for more than 12 months. Results showed that although the lymphoma patients have abnormal counts compared with controls, they differed from untreated coeliacs in that they had lower plasma cell and higher lymphocyte counts in the lamina propria and lower lymphocyte counts in the epithelium. Such changes tended to be present for up to five years before the diagnosis of lymphoma was made. The results suggest that the immunological status of coeliac patients with lymphoma differs from that of other coeliacs and it could represent a primary abnormality and also be relevant to the development of lymphoma.